CARDIOLOGY PUBLICATIONS – SUMMARY AND COMMENTS - A. A. Aleksandrovskyi (Российский кардиологический журнал, 2011)
Some typical limitations of the publications in selected Russian cardiology journals are analysed, and the potential methods to resolve these limitations are discussed.